An Energy Coordination Strategy for Island DC Microgrid With Photovoltaic and Storage System Based on Improved Consensus Algorithm - Yu DING; Aiqing YU; Chun GAO (Zhongguo dianli)
For bus voltage stability in DC microgrids, a voltage stability function for DC bus voltage is added to the multi-agent consensus algorithm.At the same time, taking the minimum operation cost of the controllable units as the objective function, combing with the conditions of power balance, a distributed energy management strategy for small photovoltaic DC microgrid is proposed to realize the optimal output of power. The distributed strategy has good convergence performance, which can effectively maintain the stability of DC microgrid. The simulation model of DC microgrid is built and the simulation results are analyzed to verify the effectiveness of the strategy.